PENGARUH HEALTH LITERACY TERHADAP PENGETAHUAN PENDAMPING MENELAN OBAT PASIEN TUBERKULOSIS DI BENGKULU - Titi A; Titin Aprilatutini; Feni Eka Dianty; Nova Yustisia (Poltekkes Kemenkes Bengkulu, 2021)
Problems: The achievement of the prevalence of pulmonary TB in Bengkulu is not yet optimal, it is still a health problem for the community. Province ranks first with 17,419 cases, while Bengkulu City ranks first with 334 souls. The independence of companions to the treatment of tuberculosis patients is very important in the tuberculosis treatment and care program at home. The aim of the research to analyze the effect of health literacy on drug swallowing assistance (PMO) for tuberculosis patients. Research method: Research design